Empathy: A Powerful Tool To Nurture Learning - Amir Prasad Behera (International Journal of Modern Agriculture, 2020)
In this paper, the relation between emotion, language, and communication is highlighted by examining the role of empathy in communication effectiveness and workplace performance. The language of Empathy is essential to develop solutions, win and retain business, and avoid or diffuse conflict among the employees. Employees need to be effective communicators to be successful in business - and in life. The professional relationship does not depend upon persuasion and motivation rather through the language of empathy. In the workplace to stay competitive, employees need to acquire empathy skills, so that they can relate effectively to diverse groups of work culture, and achieve the desired results demanded by today’s global market. The empathetic skill helps employees to understand better other peoples’ perspectives and opinions, making the work environment more enjoyable, productive, and lead to greater effectiveness. It is always believed that an effective employee increases employee optimism, motivation, and commitment, as well as organizational vision. In this study, a comprehensive literature search was performed using specific keywords. The main focus of the study was to discuss the role of empathy in communication effectiveness and workplace performance. The literature mostly published in the past ten years was included, with exception of a few landmark literatures in the field.